2020
DOI: 10.1016/j.nedt.2019.104210
|View full text |Cite
|
Sign up to set email alerts
|

Health science student teachers' perceptions of teacher competence: A qualitative study

Abstract: provided a statement (12.12.2017) that the planned research was ethically acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
(33 reference statements)
3
27
0
3
Order By: Relevance
“…Some studies believe that training teachers' professional competency and teachers' positive attitude toward classroom learning can improve teachers' complete participation rate in classroom learning (Jhang, 2019). In Kuivila's research, teacher competency included leadership and management competency, evidence-based practice competency, subject competency, ethical competency, pedagogical competency, collaboration competency, internationalization competency, and continuous professional development competency (Kuivila et al, 2020). Some scholars believe that the concept of mathematics teachers' competency includes the subject characteristics and common aspects of mathematics teachers' knowledge, skill, and belief (Blömeke et al, 2020).…”
Section: Literature Review Research On Competency Theorymentioning
confidence: 99%
“…Some studies believe that training teachers' professional competency and teachers' positive attitude toward classroom learning can improve teachers' complete participation rate in classroom learning (Jhang, 2019). In Kuivila's research, teacher competency included leadership and management competency, evidence-based practice competency, subject competency, ethical competency, pedagogical competency, collaboration competency, internationalization competency, and continuous professional development competency (Kuivila et al, 2020). Some scholars believe that the concept of mathematics teachers' competency includes the subject characteristics and common aspects of mathematics teachers' knowledge, skill, and belief (Blömeke et al, 2020).…”
Section: Literature Review Research On Competency Theorymentioning
confidence: 99%
“…A recent systematic review showed that clinical instructors' competencies are complex and as it constantly changes according to, the healthcare organizational and political structure [7]. Furthermore, organizational restructuring and emphasis on cost effectiveness has transformed the scope of CNIs' practical work and their role in clinical education [3]. Studies have also shown that required competencies for CNIs vary between countries [8].…”
Section: Introductionmentioning
confidence: 99%
“…The advances in medical sciences, the increasing numbers of nursing students, the high expectations of education and health systems, and the transfer of educational systems from hospital-based models to higher education institutes necessitate the development of the professional competencies of nursing instructors [2]. The concept of competence refers to a person's knowledge, skills, and abilities that are essential to effective performance in a job [3]. Nursing competency refers to a person's ability to perform nursing duties effectively to integrate knowledge and emotional and psychomotor skills in nursing care [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common understanding of competence includes 'knowledge', 'skills', 'attitudes', and also complex combinations of these dimensions to help people perform intelligently in speci c situations [17]. The professional competences of health science teachers are multi-dimensional, such as leadership and management competence, evidence-based education competence, subject competence, and ethical competence [18]. However, there is no agreement on the important competences required of health science teachers in different countries, even within the speci c discipline of healthcare education [19].…”
Section: Introductionmentioning
confidence: 99%